Changes in symptomatic intracranial atherosclerotic plaques and perforating arteries under medical treatment using high-resolution magnetic resonance imaging - Huijuan Miao; Leticia Simo; Liying Guo; Huimin Fan; Pan Gu; Zhaohui Song; Xiaokun Geng; Yuchuan Ding (Environmental Disease)
Objectives: Follow-up observation of changes in intracranial plaques and lenticulostriate arteries (LSAs) under the standard medical treatment can help further observe treatment effects. This study aims to observe the changes in symptomatic intracranial atherosclerosis plaques and LSAs under conventional medical treatment using high-resolution magnetic resonance imaging (HR-MRI). Subjects and Methods: Thirty-eight symptomatic middle cerebral artery stenotic patients were consecutively enrolled from October 2016 to July 2018 and HR-MRI was performed within the two weeks of the onset of acute ischemic stroke. All patients received standard medical treatment, and HR-MRI was performed at 6 months and 12 months, respectively. The characteristics of plaques and LSAs quantitative analyzed were compared before and after medical treatment. Further analysis was conducted between the subgroups of low-density lipoprotein cholesterol (LDL-C) <1.8 mmol/L and LDL-C ≥1.8 mmol/L to explore whether a lower LDL-C level is more closely associated with improvement. Results: Ultimately, 23 patients completed the first examination, and among them, 8 patients completed the second examination. After an average of 8.3 months of treatment in 23 patients, the remodeling index (1.26 ± 0.22 vs. 1.14 ± 0.16, P = 0.008), plaque volume (58.92 ± 26.61 mm3 vs. 42.26 ± 19.60 mm3, P = 0.001), plaque burden (88.29 ± 5.88% vs. 83.42 ± 11.04%, P = 0.033, enhancement volume (20.29 [16.44, 28.59] mm3 vs. 12.00 [0.00, 18.13] mm3, P = 0.000), and enhancement index (EI,0.98 ± 0.44 vs. 0.61 ± 0.48, P = 0.000) were significantly decreased compared to baseline. Repeated-measures analysis of variance showed that only the EI (P = 0.019) and the contrast of signal intensity-based on the pituitary funnel (P = 0.035) exhibited statistically significant differences among these groups. A significant difference in PB (P = 0.01) was observed between the two LDL-C subgroups. Conclusions: HR-MRI can help evaluate the medical effects, different kinds of changes on culprit plaques indicate the effectiveness of standard medical treatment. While standard medical treatment can promote the stability of plaques, the relationship between treatment and changes in LSAs remains unclear. Trial Registration: http://www.clinicaltrials.gov (identifier: NCT02719652).